Cardiac autonomic responses after resistance exercise in treated hypertensive subjects - Trevizani, Gabriela A.; Peçanha, Tiago; Nasario-Junior, Olivassé; Vianna, Jeferson M.; Silva, Lilian P.; Nadal, Jurandir (Frontiers in Physiology, 2015)
The aim of this study was to assess and to compare heart rate variability (HRV) after resistance exercise (RE) in treated hypertensive and normotensive subjects. Nine hypertensive men [HT: 58.0±7.7 years, systolic blood pressure (SBP) =133.6±6.5 mmHg, diastolic blood pressure (DBP) =87.3±8.1 mmHg; under antihypertensive treatment] and eleven normotensive men (NT: 57.1±6.0 years, SBP =127±8.5 mmHg, DBP =82.7±5.5 mmHg) performed a single session of RE (2 sets of 15-20 repetitions, 50% of 1RM, 120 s interval between sets/exercise) for the following exercises: leg extension, leg press, leg curl, bench press, seated row, triceps push-down, seated calf flexion, seated arm curl. HRV was assessed at resting and during 10 min of recovery period by calculating time (SDNN, RMSSD) and frequency domain (LF and HF) indices. Mean values of HRV indices were reduced in the post-exercise period compared to the resting period (HT: lnHF: 4.7±1.4 vs. 2.4±1.2 ms²; NT: lnHF: 4.8±1.5 vs. 2.2±1.1 ms², p<0.01). However, there was no group vs. time interaction in this response (p=0.8). The results indicate that HRV is equally suppressed after RE in normotensive and hypertensive individuals. These findings suggest that a single session of RE does not bring additional cardiac autonomic stress to treated hypertensive subjects.